A CA-repeat polymorphism close to the adenomatous polyposis coli (APC) gene offers improved diagnostic testing for familial APC. - Spirio, L (1993)
Presymptomatic genetic testing for the presence of a mutant allele causing familial adenomatous polyposis coli (APC) has been difficult to perform effectively in the past because DNA markers surrounding the APC gene on chromosome 5q have not been very informative. We report results of genetic linkage studies on both research families and clinical families by using D5S346, a highly polymorphic dinucleotide (CA)-repeat locus 30-70 kb from the APC gene. Linkage analysis with this marker in a large APC pedigree showed an increase of at least 9.0 LOD units, in likelihood of linkage of the disease-causing allele to the APC locus, when compared with the highest LOD score attained with any other closely linked marker. When the first 14 APC families that requested genotypic analysis by the DNA Diagnostic Laboratory at the University of Utah were tested with D5S346, 20 of the 31 at-risk individuals were identified as either carriers or noncarriers of an APC-predisposing allele. We see this marker as an important tool for research studies and for the presymptomatic diagnosis of APC.